Microbial and volatile profiling of soils suppressive to Fusarium culmorum of wheat. Issue 1921 (26th February 2020) - Ossowicki, Adam; Tracanna, Vittorio; Petrus, Marloes L. C.; van Wezel, Gilles; Raaijmakers, Jos M.; Medema, Marnix H.; Garbeva, Paolina
Abstract : In disease-suppressive soils, microbiota protect plants from root infections. Bacterial members of this microbiota have been shown to produce specific molecules that mediate this phenotype. To date, however, studies have focused on individual suppressive soils and the degree of natural variability of soil suppressiveness remains unclear. Here, we screened a large collection of field soils for suppressiveness to Fusarium culmorum using wheat ( Triticum aestivum ) as a model host plant. A high variation of disease suppressiveness was observed, with 14% showing a clear suppressive phenotype. The microbiological basis of suppressiveness to F. culmorum was confirmed by gamma sterilization and soil transplantation. Amplicon sequencing revealed diverse bacterial taxonomic compositions and no specific taxa were found exclusively enriched in all suppressive soils. Nonetheless, co-occurrence network analysis revealed that two suppressive soils shared an overrepresented bacterial guild dominated by various Acidobacteria. In addition, our study revealed that volatile emission may contribute to suppression, but not for all suppressive soils. Our study raises new questions regarding the possible mechanistic variability of disease-suppressive phenotypes across physico-chemically different soils. Accordingly, we anticipate that larger-scale soil profiling, along with functional studies, will enable a deeper understanding of disease-suppressive microbiomes.